Binarity of the LBV HR Car. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Rivinius, Th.; Boffin, H. M. J.; de Wit, W. J.; Mehner, A.; Martayan, Ch.; Guieu, S.; Le Bouquin, J.-B.
Abstract: VLTI/AMBER and VLTI/PIONIER observations of the LBV HR Car show an interferometric signature that could not possibly be explained by an extended wind, more or less symmetrically distributed around a single object. Instead, observations both in the Brγ line and the H -band continuum are best explained by two point sources (or alternatively one point source and one slightly extended source) at about 2 mas separation and a contrast ratio of about 1:5. These observations establish that HR Car is a binary, but further interpretation will only be possible with future observations to constrain the orbit. Under the assumption that the current separation is close to the maximum one, the orbital period can be estimated to be of the order of 5 years, similar as in the η Car system. This would make HR Car the second such LBV binary.